The Climate Change Impacts on Water Resources and Crop Yield - Niknamian, Sorush (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
This research evaluated climate change impacts on temperature, precipitation, and runoff using LARS-WG and SWAT models under climate scenarios. First, drought intensity was calculated for the period 1987-2016. Then, the LARS-WG model was calibrated to generate climatological data for future periods. The coefficients of precipitation as well as minimum and maximum temperature changes were simulated as SWAT model inputs. The results of LARS-WG model indicated that temperature will increase in future periods and that changes will occur not only in precipitation rate but also in its pattern. Then, changes in runoff were simulated by introducing downscaled results to SWAT model. The model was calibrated and validated by SWAT-CUP software. Nash-Sutcliffe (NS) coefficients (0.58 and 0.49) and R2 determination coefficients (0.65 and 0.50) were obtained for calibration and validation periods, respectively. The results showed that runoff will increase in spring and summer during 2011-2030 period, but it will decrease in fall and winter. Further, runoff will rise in fall and winter while it will drop in spring and summer throughout 2046-2065 and 2080-2099 periods under all three scenarios. Such seasonal shifts in runoff levels result from climate change consequences in the forms of temperature rise, snowmelt, altered precipitation pattern, etc. Future-period evapotranspiration will rise under all three scenarios with a maximum increase in 2080-2099 period under A2 scenario. Additionally, rainfed crop yields will decline without considerable changes in irrigated and horticultural crop yields.